Kajian Peran Masyarakat dalam Pengelolaan Sumber Daya Alam di Kawasan Desa Hatu Kecamatan Leihitu Barat Kabupaten Maluku Tengah - Matly, Maria Lidwina; Sihasale, Daniel Anthoni; Lasaiba, Mohammad Amin (JENDELA PENGETAHUAN, 2026)
This study was motivated by the increasing pressure on natural resources in coastal and forest areas of Maluku, demanding a community-based approach to maintain ecosystem sustainability. The research aims to analyze the role of Hatu Village’s community in natural resource management through the traditional sasi system and its collaboration with the village government. A qualitative descriptive method was applied using participatory observation, in-depth interviews, and documentation to understand social dynamics, cultural values, and ecological practices. The findings show that the community actively maintains ecological balance through sasi implementation, customary forest supervision, and environmental education based on local values. Customary institutions such as kewang serve effectively as moral and social regulators in environmental governance. The study confirms that the integration of customary systems and village policies creates adaptive, efficient, and equitable ecological governance. It implies the necessity of formal recognition of customary institutions in conservation policies